Epiphytic microbiota of apple in integrated and organic growing - Pintér, Sz.; Benczer, J.; Szabó, Z.; Nyéki, J. (International Journal of Horticultural Science, 2010)
The surface microbial contamination is of great interest in case of fruits, since they are they potential sources of spoilage or foodborne diseases. The aim of this work was to compare the epiphytic microbiota of food safety concern of different apple cultivars as a function of cultivation methods (organic versus integrated), production year and place. Investigating 47 samples it was found that the average microbial contamination of the apple surfaces was within a certain range,, practically independent of cultivar, growing area and year. The frequency distribution of the surface bacterial, mould and yeast counts did not show significant differences between growing technologies or varieties. The principal component analysis the samples ranked the apple samples into seven groups on the basis of their microbial contamination level, and the discriminant analysis proved the goodness of grouping. The grouping was independent from cultivars and growing methods. No foodborne pathogen Salmonella spp. and Listeria spp. were found on the surfaces of apples.